2015
DOI: 10.1001/jamasurg.2015.1126
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Targets for Regional Variation in Surgical End-Stage Renal Disease Care

Abstract: Marked regional variation in functional incident AVF frequency and risk-adjusted ESRD mortality exists across the United States. Differences in access to preoperative nephrology care and patient comorbidities may explain some of these variations, but an opportunity to implement best-practice guidelines exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…examined the presence of incident functional arteriovenous fistula in a cohort of 464,547 patients beginning hemodialysis, and found marked regional variation in incident functional arteriovenous fistula, and risk-adjusted ESRD mortality among ESRD networks where the networks representing Texas and other areas in the American South had the lowest percentage in incident arteriovenous fistula and highest mortality risk. 37 Furthermore, analyses by Yan et al. showed that Middle Atlantic and Southern states exhibited lower than average probability of receipt of pre-ESRD nephrology care; 18 , 19 interestingly, these areas correspond to some of the clusters identified in our report.…”
Section: Discussionsupporting
confidence: 71%
“…examined the presence of incident functional arteriovenous fistula in a cohort of 464,547 patients beginning hemodialysis, and found marked regional variation in incident functional arteriovenous fistula, and risk-adjusted ESRD mortality among ESRD networks where the networks representing Texas and other areas in the American South had the lowest percentage in incident arteriovenous fistula and highest mortality risk. 37 Furthermore, analyses by Yan et al. showed that Middle Atlantic and Southern states exhibited lower than average probability of receipt of pre-ESRD nephrology care; 18 , 19 interestingly, these areas correspond to some of the clusters identified in our report.…”
Section: Discussionsupporting
confidence: 71%
“…Multiple prior studies have identified longer duration of pre-dialysis nephrology care as the strongest predictor of decreasing incident CVC use. [ 2 , 10 , 19 23 ] This graded association was significant in our cohort as well, supporting an assertion that earlier nephrology referrals are key to increasing rates of incident AVF usage, regardless of the population. In addition, we observed a strong association between uninsured status and higher incident CVC use in our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…National data reveal substantial variation in incident AVF rates from 11.1% to 22.2% among regional ESRD networks, and significant disparities in incident AVF use by race, gender, and insurance status [ 9 , 10 ]. Because blacks, Hispanics, women, and the uninsured are significantly less likely to have a functioning AVF at the time of HD initiation, these vulnerable populations disproportionately bear the burden of complications due to CVC use.…”
Section: Introductionmentioning
confidence: 99%
“…Slinin et al found that survival at one year after HD initiation was associated with the number of evidence-based KDOQI guidelines met, and also found that 81% of incident HD patients began HD with an HC, despite more than 57% being in the care of a nephrologist prior to initiation of HD [17]. Indeed, Zarkowsky et al found that there is marked regional variation in AVF placement [18] and that a third of ESRD patients initiating HD with an HC had been in the care of a nephrologist for over six months [19]. This has led to the creation of simulation models to help nephrologists predict when to refer for AVF placement [20], however we found that initiating HD with an HC remained common.…”
Section: Discussionmentioning
confidence: 99%